2008
DOI: 10.1186/1472-6939-9-14
|View full text |Cite
|
Sign up to set email alerts
|

Patients' perception and actual practice of informed consent, privacy and confidentiality in general medical outpatient departments of two tertiary care hospitals of Lahore

Abstract: Background: The principles of informed consent, confidentiality and privacy are often neglected during patient care in developing countries. We assessed the degree to which doctors in Lahore adhere to these principles during outpatient consultations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
69
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 26 publications
4
69
3
Order By: Relevance
“…The same study reported that psychosocial privacy was observed in 31.9% of cases and that informational privacy was observed in 30.6% of cases, which was lower than that (41.58%) found in the present study. In a study conducted in Lahore, only 10.8% of public hospitals maintained patient data confidentiality (22), which was lower than that in the present study. The poor level of confidentiality was attributed to the large number of patients in the hospitals making it difficult for physicians to observe all confidentiality protocols, in addition to large numbers of beds in rooms, examinations without curtains, and physicians observing and examining patients in the presence of others.…”
Section: Discussioncontrasting
confidence: 51%
“…The same study reported that psychosocial privacy was observed in 31.9% of cases and that informational privacy was observed in 30.6% of cases, which was lower than that (41.58%) found in the present study. In a study conducted in Lahore, only 10.8% of public hospitals maintained patient data confidentiality (22), which was lower than that in the present study. The poor level of confidentiality was attributed to the large number of patients in the hospitals making it difficult for physicians to observe all confidentiality protocols, in addition to large numbers of beds in rooms, examinations without curtains, and physicians observing and examining patients in the presence of others.…”
Section: Discussioncontrasting
confidence: 51%
“…Failure to observe this may cause embarrassment to both patients and providers. Other studies have also reported the importance of privacy and confidentiality (Humayun et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In some developing countries, the value patients place on informed consent is often not paralleled by physicians, and medical paternalism is especially prevalent among those working with illiterate populations. [13][14][15] A review article by Bastia attempted to clarify common misconceptions among Indian physicians regarding what constitutes appropriate informed consent. 16 In our study, a detailed, comprehensive, and patientappropriate informed consent with or without a visual aid resulted in significantly higher scores from preinformed consent to post-informed consent.…”
Section: Discussionmentioning
confidence: 99%